2019
DOI: 10.1097/jhq.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Shared Care During Breast and Colorectal Cancer Treatment: Is It Associated With Patient-Reported Care Quality?

Abstract: There is growing evidence that shared care, where the oncologist, primary care physician, and/or other specialty physicians jointly participate in care, can improve the quality of patients' cancer care. This cross-sectional study of breast and colorectal cancer patients (N = 534) recruited from the New Jersey State Cancer Registry examined patient and health system factors associated with receipt of shared care during cancer treatment into the early survivorship phase. We also assessed whether shared care was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Details of the study have been reported previously. 32 Stratified random sampling by cancer site and year of diagnosis were used to identify potential study participants for this study. Eligibility criteria for breast cancer survivors were: (1) diagnosis between 2012 and 2014; (2) a primary, non-metastatic breast cancer with no previous history of cancer; (3) cancer stages I, II, III at diagnosis; (4) aged 21–79 years at diagnosis; (5) alive at time of contact and residing in New Jersey at diagnosis; and (6) able to read and write English.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the study have been reported previously. 32 Stratified random sampling by cancer site and year of diagnosis were used to identify potential study participants for this study. Eligibility criteria for breast cancer survivors were: (1) diagnosis between 2012 and 2014; (2) a primary, non-metastatic breast cancer with no previous history of cancer; (3) cancer stages I, II, III at diagnosis; (4) aged 21–79 years at diagnosis; (5) alive at time of contact and residing in New Jersey at diagnosis; and (6) able to read and write English.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the proportion of patients with shared care was higher (90%) in our study population compared with two previous studies (66% and 62%). 25,26 The difference may be due to the fact that these two studies used patient-reported data with different demographic and cancer populations. Prior studies have not focused on racial/ethnic minorities, while this study focused on Black women who have a higher prevalence of comorbidities at breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found that 30-50% of breast cancer patients had shared care during cancer care. 25,26 Limited studies of shared care have demonstrated improved symptom management, treatment initiation, adherence, and quality cancer care. 21,23,27,28 The importance of shared care is recognized by national cancer organizations as a key component for the delivery of high-quality care.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies (92%) occurred during active treatment and 5 studies (38%) during survivorship (posttreatment). All U.S. studies explicitly stated that racial or ethnic minorities were included, [23][24][25][26][27][28][29][30] ranging from 20% to 100% of the study population. Four studies focused on populations that experience health and healthcare disparities, specifically Hispanic and Black cancer survivors.…”
Section: Characteristics Of the Studies And Study Populationsmentioning
confidence: 99%
“…Five studies described boundary status, which is the proportion of teams working in the same or different healthcare practices or health systems. 23,29,[32][33][34] These studies stated the proportion of patients who sought care with a clinician outside the study team. Geographic dispersion, the degree to which teams are colocated or dispersed across healthcare settings, was described in one study that examined care within and outside the same state.…”
Section: Teamwork Conceptsmentioning
confidence: 99%